KEMITRAAN MASYARAKAT DENGAN PENGELOLA PABRIK GULA CAMMING DALAM PENGADAAN BAHAN BAKU DI KABUPATEN BONE - Sari, Andi Aswinda; Fatmawati, Fatmawati; Malik, Ihyani (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACT This study aims to determine the partnership between the community and the government in the procurement of raw materials at the Camming Sugar Factory, Bone Regency. The number of informants in this study were 6 people. This study uses a qualitative type with a phenomenological type of research, which is a form of research that emphasizes the subjectivity of human life experience to reveal events or facts, phenomena, and circumstances that occur during the research. Data collection techniques using the method of observation, interviews and documentation. The results of this study indicate that the form of partnership pattern that is carried out between partner farmers and the Camming Sugar Factory is a plasma core partnership pattern in which PG Camming is the core party and partner farmers are the plasma party. The results of the study also indicate the level of satisfaction of partner farmers with the partnership pattern with the Camming Sugar Factory. The partnership built between sugarcane farmers and the Camming Sugar Factory is to make contract agreements, provide professional services and assistance, not to give special rewards between sugar cane farmers and Camming Sugar Mills. They establish a partnership relationship by mutually benefiting without anyone being harmed. Keywords: Partnership, Commitment and Communication.